2014
DOI: 10.1590/1807-1929/agriambi.v18n09p881-886
|View full text |Cite
|
Sign up to set email alerts
|

Aplicações sucessivas de lodo de esgoto no girassol e efeito residual no trigo e triticale

Abstract: R E S U M ONeste trabalho se propôs avaliar o efeito da aplicação do lodo de esgoto durante dois anos sucessivos, na cultura do girassol e seu efeito residual na produtividade do trigo e triticale. Trabalhou-se durante dois anos consecutivos com a cultura do girassol semeando-se, após a colheita do segundo ano, o trigo e o triticale sem aplicação de lodo de esgoto. Foi adotado o delineamento experimental em blocos casualizados constituído por 6 tratamentos e 5 repetições: T0 -sem adubação com nitrogênio; T1 -a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In the same way, the oil content of the seeds is a determining factor from the economic point of view of N application up to the maximum threshold of 32 applications in the cycle. Opposite results were found by Lobo et al (2014b), when evaluating the effect of N on the production variables of sunflower plants, and concluded that there was no significant difference for the oil content. On the other hand, Gomes et al (2012) using different doses of N in the canola crop, concluded that N had an influence on the oil content of the seeds, which ensures the importance of using this macronutrient to achieve high levels of oil in the crop.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…In the same way, the oil content of the seeds is a determining factor from the economic point of view of N application up to the maximum threshold of 32 applications in the cycle. Opposite results were found by Lobo et al (2014b), when evaluating the effect of N on the production variables of sunflower plants, and concluded that there was no significant difference for the oil content. On the other hand, Gomes et al (2012) using different doses of N in the canola crop, concluded that N had an influence on the oil content of the seeds, which ensures the importance of using this macronutrient to achieve high levels of oil in the crop.…”
Section: Resultsmentioning
confidence: 87%
“…These results differed from those achieved in this work as this variable was influenced by the number of nitrogen-dose applications through fertigation for a 100 kg ha -1 N dose. On the other hand, Lobo et al (2014b) observed a linear increase in the one-thousand seed mass of sunflower with nitrogen application.…”
Section: Resultsmentioning
confidence: 94%